Konsep Kemudahan dalam Hukum Perspektif Al Quran dan Hadist - A. Malthuf Siroj (Universitas Nurul Jadid, 2019)
Every law has its own features and characteristics that reflect its identity and essence, Islamic law is no exception. One of the peculiarities of Islamic law is that it is rabbani (not man-made), comprehensive, easy, realistic, there is no legal imposition beyond human capability, and it's moderate. The characteristics of Islamic law in addition to showing the value of compassion (mercy), also makes the Sharia brought by the Prophet Muhammad always survives and relevant in every place, time and circumstance. Al-Qur'an and Hadith as two main sources of Islamic teachings explain a lot, both explicitly and implicitly, about the principle of ease in law. This is a form of Islamic attention to the situations and conditions experienced by humans that are relatively different in relation to the practice of Islamic teachings. From the two sources of the Shari'a the scholars formulated a number of rules which substantively contained the spirit of ease in law. So that even in difficult and narrow conditions, Islam guarantees its adherents not to come out of the Shari'a frame with an alternative dispensation called rukhshah.Keywords: Ease, law, rukhshah, al-Qur’an, hadith